1.
substitution x+y=8, x−y=−4
1.
substitution x+y=8, x−y=−4
2.
substitution 3x−4y=−30, 3x+2y=6
2.
substitution 3x−4y=−30, 3x+2y=6
3.
substitution −4x+9y=9, x−3y=−6
3.
substitution −4x+9y=9, x−3y=−6
4.
substitution 12x+13y=9, 15x−23y=6
4.
substitution 12x+13y=9, 15x−23y=6
5.
substitution −2a+3b=14, a−4b=3
5.
substitution −2a+3b=14, a−4b=3
6.
substitution 3x−7y=27, −5x+4y=−45
6.
substitution 3x−7y=27, −5x+4y=−45
7.
substitution 3x−4y=100, x3 +4y3 =100
7.
substitution 3x−4y=100, x3 +4y3 =100
8.
substitution y=3x−4, y=32 x−2
8.
substitution y=3x−4, y=32 x−2
9.
substitution x2 −y2 =−1, x+4y=−12
9.
substitution x2 −y2 =−1, x+4y=−12
10.
substitution 12 x+17 y=4, 16 x−27 y=−1
10.
substitution 12 x+17 y=4, 16 x−27 y=−1